KARAKTERISTIK PENDERITA MIOMA UTERI RAWAT INAP DI RSUD DELI SERDANG LUBUK PAKAM TAHUN 2013-2015 - yuli anti sipayung; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Uterine myoma are also known as fibromioma, fibroids, or leiomyomas are benign neoplasm derived from uterine smooth muscle and connective tissue on it. Most of them was found with an estimated incidence of 20% -40% in women during reproductive years. In Indonesia, uterine myoma was found 2.4% - 11.7% of all gynecological patients were treated. In Deli Serdang Hospital Lubuk Pakam there are 78 cases of uterine myoma during 2013-2015. The research is descriptive with case series design. Population and sample were 78 data (total sampling) by using secondary data obtained from medical records of patients with uterine myoma. The results showed the proportion of patients with uterine myoma highest age 35-44 years old 44.9%, Javanese 66.9%, senior high school 35.9%, housewives 75.6%, married status 88.5%. menarche age > 12 years was 37.2%, multiparous parity47.4%, type of submucosal fibroids 25.6%, having more than one complaint 42.3%, hemoglobin <12 g/dl (79.5%), hysterectomy 55, 1%, the average length of stay 8 days, discharged under medical treatment 93.6%, government funding source 92.3%. The proportion aged based on the type of uterine myoma highest age > 44 years old. The proportion of patients with uterine myoma with the type of submucous fibroids, abnormal bleeding 60%, hemoglobin <12 g/dl (85%) and hysterectomy55%, the type of intramural fibroids having more than one complaint 81.8%, hemoglobin <12 g/dl (72.7%) and hysterectomy 54.5%, the type of subserosal fibroids having more than one complaint 50% and conservative treatment 50%, the type of multiple fibroids having more than one complaint 88.9%, hemoglobin <12 g/dl 88.9% and hysterectomy 77.8%. It was suggested that women who have risk factors for uterine myoma especially women in the reproductive age and multiparity to maintain in their health with a healthy diet and regular check-up for early detection of the possibility of the discovery of uterine myoma. For Deli Serdang Hospital Lubuk Pakam to complete data in the medical record including menarche age of patients, parity, and the type of myoma uteri. Keywords: uterine myomas, Characteristics of Patients